CATOSTYLUS OUWENSI (RHIZOSTOMEAE, CATOSTYLIDAE), A NEW JELLYFISH FROM IRIAN (NEW GUINEA) AND OUWENSIA CATOSTYLI n, gen., n, sp., PARASITIC IN C.OUWENSI - MOESTAFA, SITI HADIDJAH; McCONNAUGHEY, BAYARD H (Research Center for Biology, 1966)
-